2016
DOI: 10.1302/2046-3758.59.2000500
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of statins in preventing glucocorticoid-related osteonecrosis in animal models

Abstract: ObjectivesThe primary purpose of this meta-analysis was to determine whether statin usage could reduce the risk of glucocorticoid-related osteonecrosis in animal models.MethodsA systematic literature search up to May 2015 was carried out using the PubMed, Ovid, EBM reviews, ISI Web of Science, EBSCO, CBM, CNKI databases with the term and boolean operators: statins and osteonecrosis in all fields. Risk ratio (RR), as the risk estimate of specific outcome, was calculated along with 95% confidence intervals (CI).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…A meta-analysis suggested that statins usage decreased the risk of GC-related ON. 42 However, we still cannot determine the protective effect of statins in treating ON patients unless some high-quality clinical trials are performed. Bisphosphonates as another hot discussion pharmacologic agent may protect major joints from necrosis by inhibiting the bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis suggested that statins usage decreased the risk of GC-related ON. 42 However, we still cannot determine the protective effect of statins in treating ON patients unless some high-quality clinical trials are performed. Bisphosphonates as another hot discussion pharmacologic agent may protect major joints from necrosis by inhibiting the bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the question remains: does reducing circulating LDL effectively reduce the risk of SONFH with steroid application? In animal models, it has been suggested that reduced circulating lipid levels can reduce the risk of SONFH (Yang Z. et al, 2016), but the clinical effect remains to be confirmed. Additionally, in the location subgroup analysis of rs1042031 results, the heterogeneity decreased significantly from 50 to 0%.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-coagulant ingredient warfarin and hypolipidemic drug statins can significantly decrease the risk of ON induced by steroids. [ 25 27 ] In addition, physical therapies such as extracorporeal shockwave therapy (ESWT), hyperbaric oxygen therapy, and pulsed electromagnetic therapy have been proved to stimulate neovascularization, increase intracellular oxygen, and reduce inflammation reactions in ON lesions. [ 28 31 ] Implantation of autologous bone marrow mesenchymal stem cells is a promising treatment of osteonecrosis of femoral head, significantly reducing the risk of femoral head collapse and the need of total hip replacement.…”
Section: Discussionmentioning
confidence: 99%